2018
DOI: 10.1017/s0033291718002313
|View full text |Cite
|
Sign up to set email alerts
|

Attention to threat in posttraumatic stress disorder as indexed by eye-tracking indices: a systematic review

Abstract: This review is the first to systematically evaluate extant findings in PTSD emanating from eye-tracking studies employing group-comparison designs. Results suggest that sustained attention on threat might serve as a potential target for therapeutic intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
69
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(81 citation statements)
references
References 170 publications
(500 reference statements)
11
69
1
Order By: Relevance
“…While attempting to address this by including depressive symptoms and a functioning measure, many other non-symptoms may play a causal role in PTSD, as well as in bridging PTSD and other disorders (Jones et al, 2017). These may include, among others, threat-related cognitive biases (Lazarov et al, 2018(Lazarov et al, , 2019, neural abnormalities (O'Doherty et al, 2015;Koch et al, 2016), social functioning (Wilcox, 2010), and other factors which have been implicated in PTSD such as age (Konnert and Wong, 2015) and gender (Lehavot et al, 2018). Thus, future network-based research should include additional non-symptom nodes to enrich our understanding of PTSD (Jones et al, 2017).…”
mentioning
confidence: 99%
“…While attempting to address this by including depressive symptoms and a functioning measure, many other non-symptoms may play a causal role in PTSD, as well as in bridging PTSD and other disorders (Jones et al, 2017). These may include, among others, threat-related cognitive biases (Lazarov et al, 2018(Lazarov et al, , 2019, neural abnormalities (O'Doherty et al, 2015;Koch et al, 2016), social functioning (Wilcox, 2010), and other factors which have been implicated in PTSD such as age (Konnert and Wong, 2015) and gender (Lehavot et al, 2018). Thus, future network-based research should include additional non-symptom nodes to enrich our understanding of PTSD (Jones et al, 2017).…”
mentioning
confidence: 99%
“…When associations were examined based on individual symptom clusters of PTSD, we found differential associations based on attention bias indices: PTSD avoidance symptom severity was associated with greater initial fixation to angry expressions than neutral expressions and re-experiencing symptom severity was associated with longer dwell duration to angry expressions than neutral expressions. Previous studies have shown a fairly consistent pattern of sustained attention to threatening stimuli in individuals with PTSD (see Lazarov et al, 2018, for a meta-analytic review); this includes our own research indicating attention biases toward threatrelated stimuli (angry faces; . In this sample of chronically traumatized African American women utilizing services in an urban hospital, we found further support for that pattern, observing significantly greater dwell duration toward angry emotional stimuli compared to neutral stimuli.…”
Section: Discussionmentioning
confidence: 94%
“…Studies in civilian and veteran samples have found evidence that PTSD (or higher levels of PTSD symptoms) is associated with initial and sustained attention for threatening cues (Armstrong, Bilsky, Zhao, & Olatunji, 2013;Kimble, Fleming, Bandy, Kim, & Zambetti, 2010;Thomas, Goegan, Newman, Arndt, & Sears, 2013). A recent meta-analysis including 11 eye tracking studies of PTSD found support for sustained attention to threat among individuals with PTSD compared to those without PTSD (Lazarov et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generalized defense and hypervigilance consequent to mOFC damage present similarly to symptoms seen in GAD (Newman et al, 2013) or panic disorder (Lieberman et al, 2016). On the other hand, stimulus-specific hyper-reactivity following lOFC damage appears to be more akin to the symptoms of post-traumatic stress disorder (Lazarov et al, 2019), specific phobia (Hermann et al, 2009), or obsessive-compulsive disorders (Sizino da Victoria et al, 2012; e.g., defensive responses in response to specific "triggering" events or stimuli). Though this interpretation oversimplifies the complexity of anxiety disorder subtypes, it highlights the need for frameworks that propose unique neural substrates underlying distinct symptoms within a common class of disorders (e.g., anxiety).…”
Section: Contribution Of Ofc Subregions To Anxiety Disordersmentioning
confidence: 99%